Treatment goals in ANCA-associated vasculitis: defining success in a new era - Alberici, Federico; Tedesco, Martina; Popov, Tamara; Balcells-Oliver, Monica; Mescia, Federica (Frontiers in Immunology, 2024)
Antineutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV) is a group of rare diseases characterized by small vessel inflammation. The lungs and kidneys are commonly affected, with the potential for organ damage to reach clinically meaningful levels. Glucocorticoids and immunosuppressive drugs have modified the disease course of AAV; instead of being a disease characterized by high mortality rates, it is now considered to be a chronic condition. This has, however, come at the cost of numerous potential treatment-related side-effects. Consequently, the patient journey throughout the disease course is frequently characterized by drug-induced toxicity ranging from effects that, although not clinically concerning, are severely unpleasant, such as dizziness, insomnia, mood changes and nausea, to effects with the potential for more clinically relevant consequences, such as severe infection, cardiovascular disease, and osteoporosis. Overshadowed by the success of achieving meaningful impact on the disease course, combined with the lack of effective alternatives, consideration of the burden of side effects on the patient has been characterized by a degree of indifference. This paper reviews the potential for treatment-related side effects in AAV, explores available tools for evaluating their impact on the patient and re-evaluates the criteria for defining treatment success in AAV.